Kemampuan Numerasi Siswa SMP/MTs yang Bergaya Belajar Visual, Auditorial, dan Kinestetik pada Konten Pengukuran dan Geometri - Resti Elmi Mubarkah; Masriyah Masriyah (Program Studi S1 Matematika UNESA, 2023)
UNESCO emphasizes that one of the determinants of the progress of a nation is numeracy skills. The numeracy skills of Indonesian students are still unsatisfactory. Students' understanding of measurement and geometry content is very low so their learning outcomes are also low. Low numeracy skills and poor understanding of the material in measurement and geometry content are caused by various things, such as learning styles. Each student has a different learning style, such as visual, auditory, and kinesthetic learning styles. This research is qualitative descriptive research according to its aim to describe the numeracy abilities of SMP/MTs students with visual, auditory, and kinesthetic learning styles in measurement and geometry content. The subjects of this study were three students of class VIII-B at MTs Negeri 1 Magetan with different learning styles and equal mathematical abilities. Methods of data collection in this study are through a learning style questionnaire, written tests, and interviews. The written test is in the form of a math ability test and a numeration assignment. The results of this study were: 1) student with a visual learning style mastered the indicators of communication skills, mathematization, choosing strategies to solve problems, and using language and symbolic, formal, and technical operations while indicators of numeracy skills that were not mastered were indicators of representational and reasoning abilities and argument; 2) student with an auditory learning style master indicators of communication skills, mathematization, and choosing strategies to solve problems while indicators of numeracy skills that are not mastered are indicators of representation, reasoning and argument abilities, and using language and symbolic, formal, and technical operations; 3) student with a kinesthetic learning style only master indicators of mathematical ability and choose strategies to solve problems while indicators of numeracy skills that are not mastered are indicators of communication, representation, reasoning and argument abilities, and using language and symbolic, formal, and technical operations.